Sobre la naturaleza o carácter inmaterial del alma humana - Guzmán Vicente Burgoa, Lorenzo de ca. 21. Jh. (Sapientia, 2011)
Tomas Aquinas stated that awareness of the existence of the soul is something evident as it is reflected in the act of the thinking ego. However, it is difficult to know what it is or its nature. In fact, it is of our utmost interest to determine that nature of our soul as it is part of knowledge of ourselves. We will finally conclude together with Aristotle “the soul is not a body nor can it be found without a body”.